FRIENDS IN HIGH PLACES: THE U.S. CONTRIBUTION TO COSTA RICA STATE-BUILDING IN THE FIGUERES YEARS - Fink, Leon (2021)
José Figueres’s rise to power as president in Costa Rica in 1953, his enemies activities in Nicaragua to overthrow him, and his confrontation with Anastasio Somoza are well known facts. Less well-known, perhaps, is the role of certain U.S. actors -especially “liberal Democrats”- who helped protect the Figueres regime from would-be hostile actors in the U.S. and elsewhere in the region as well as within the country itself.  In this paper, I concentrate on the role of influential New Deal economist and former secretary of state for Latin American Affairs Adolf Berle.